(untitled) (Alternate Horizons, 2021)
Food systems across the world have changed from wholesome foods to fast and ultrarefined foods. This nutrition transition has contributed immensely to the rapidly increasing Non-Communicable Diseases (NCDs) such as diabetes and obesity across the globe. There is a growing need to support consumers in making healthier food choices through information, education and communication, and by targeting the market environment through food labelling. Food labels include ingredients, amounts, allergens, name of the manufacturer, country of origin, date of manufacture and expiry. This article aims to raise awareness of the effectiveness of food labelling to improve the food system and, in return, combat the rising NCDs. Nutrition labelling has shown positive results in shaping consumer food choices and improving the quality of food production by food manufacturers. Unfortunately, there is a tendency for food companies to market false information about food, marketing an item to consumers as a healthy food option, when in fact, it is not. Despite increasing calls for mandatory food labelling as a policy strategy to halt the rising prevalence of NCDs, governments require clear evidence supporting the effectiveness of food labelling in improving food choices to make informed decisions. Mandatory labelling would require a strong commitment from all stakeholders, including the food industry, governments, consumer organisations and the trade industry.